1980
DOI: 10.1093/oxfordjournals.jbchem.a132803
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thermoglucosidius α-Glucosidase: Temperature Dependence of Activity and Stability1

Abstract: A p-nitrophenyl-alpha-D-glucopyranoside-hydrolyzing alpha-glucosidase from an obligate thermophile, Bacillus thermoglucosidius KP 1006, gave a triphasic relationship at pH 6.8 in the van't Hoff plot of Km, in the Arrhenius plot of the first order rate constant of inactivation with 0.1% sodium dodecyl sulfate, and in the logarithmic plot of the maximal fluorescence intensity at 346 nm versus reciprocal of temperature. The respective plots exhibited two breaks at 40 and 61 degrees C, 43 and 62 degrees C, and 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An alternative explanation is that the type of CIN that progresses to cancer is metabolically different from CIN that does not show this progression. An increase in PC concentrations has been shown in immortalised Schwann cells virally transfected with oncogenes SV40 (24), and specific enzyme activities in phosphatidylcholine synthesis are increased in virally infected cells compared with control cells (24,25). In the development of invasive cervical cancer, genomic integration of oncogenic human papillomavirus appears to be an important genetic event (26); two viral proteins, E6 and E7, alter cell cycle control and are implicated in human papillomavirus-induced oncogenesis (27).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that the type of CIN that progresses to cancer is metabolically different from CIN that does not show this progression. An increase in PC concentrations has been shown in immortalised Schwann cells virally transfected with oncogenes SV40 (24), and specific enzyme activities in phosphatidylcholine synthesis are increased in virally infected cells compared with control cells (24,25). In the development of invasive cervical cancer, genomic integration of oncogenic human papillomavirus appears to be an important genetic event (26); two viral proteins, E6 and E7, alter cell cycle control and are implicated in human papillomavirus-induced oncogenesis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be several different unfolded forms, these different forms will all be inactive and not distinguishable from each other by activity assays. In the case of the enzyme α-glucosidase isolated from the bacterial thermophile Bacillus thermoglucosidius, the incorporation of a reversible and irreversible pathway into the kinetic model resulted in linear Arrhenius plots for the rate constants for each process (Suzuki, Nakamura, Kishigami, & Abe, 1980;Yoshioka, Izutsu, Aso, & Takeda, 1991).…”
Section: Complexity Of Stability Determinations During Formulation Dementioning
confidence: 99%
“…4A)]. Arrhenius plots of ν values of fructose release [23] showed that the apparent activation energy (at pH 5.0) was 160 kJ/mol at 30-40°C and 32 kJ/mol at 40-60°C. The enzyme was stable up to 60°C for 10 min at pH 7.0 (Fig.…”
Section: Catalytic Properties Of B Stearothermophilus Kp1289 Inulinamentioning
confidence: 99%